Why the rich get richer and the poor get poorer - Mantel, Rolf (Estudios de Economía, 2016)
The usual procedure in the field of optimal growth consists in maximizing a (discounted or not) sum of instantaneous utilities, called welfare. Such an optimality criterion implies that preferences are independent over time. Following in the tradition of Irwing Fisher, Koopmans presented an alternative for the case of discrete time periods.